2017
DOI: 10.1038/nn.4553
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala inputs to prefrontal cortex guide behavior amid conflicting cues of reward and punishment

Abstract: Orchestrating appropriate behavioral responses in the face of competing signals that predict either rewards or threats in the environment is crucial for survival. The basolateral amygdala (BLA) and prelimbic (PL) medial prefrontal cortex (mPFC) have been implicated in reward-seeking and fear-related responses, but how information flows between these reciprocally-connected structures to coordinate behavior is unknown. We recorded neuronal activity from the BLA and PL while rats performed a task where in shock- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
214
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 262 publications
(243 citation statements)
references
References 72 publications
21
214
2
2
Order By: Relevance
“…“Winner-take-all” effects have been observed in multisensory decision-making [8,9], while our summation model predicts that the influence of each modality should grow smoothly with intensity. To examine the effects of intensity, we presented real flies with single and multimodal stimuli at higher and lower wind speeds ( N = 11, 11, and 12 for wind at 10, 25, and 45 cm/s, respectively), while holding visual stimulus intensity constant.…”
Section: Resultsmentioning
confidence: 87%
“…“Winner-take-all” effects have been observed in multisensory decision-making [8,9], while our summation model predicts that the influence of each modality should grow smoothly with intensity. To examine the effects of intensity, we presented real flies with single and multimodal stimuli at higher and lower wind speeds ( N = 11, 11, and 12 for wind at 10, 25, and 45 cm/s, respectively), while holding visual stimulus intensity constant.…”
Section: Resultsmentioning
confidence: 87%
“…To directly test the hypothesis that socially-derived information about the aversive cue is transmitted from the ACC to the BLA during observational conditioning, we used an intersectional viral strategy (Senn et al, 2014) to express Channelrhodopsin-2 (ChR2) in ACC neurons that monosynaptically project to the BLA (Figure 4A–B) (Burgos-Robles et al, 2017). Ex vivo recordings demonstrated that ChR2-expressing neurons fired action potentials in response to blue light while non-expressing neighbors showed no response (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Burgos‐Robles et al . () inhibited the projection from the basolateral amygdala to the prelimbic cortex using a combination of CAV and the human M 4 (hM4Di) DREADD to demonstrate a functional role for this pathway in fear‐associated memories. The AAV serotype 2/5 has also been shown to have retrograde tropism (Aschauer et al ., ).…”
Section: Viral Methods For Chemogenetic Receptor Expressionmentioning
confidence: 99%